Cognitive uncertainty and overconfidence - Andrea Amelio (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Overconfidence is one of the most ubiquitous cognitive bias. There is copious evidence of overconfidence being relevant in a diverse set of economic domains. In this paper, we relate the recent concept of cognitive uncertainty with overconfidence. Cognitive uncertainty represents a decision maker's uncertainty about her action optimality. We present a simple model of overconfidence based on the concept of cognitive uncertainty. The model relates the concepts theoretically and generates testable predictions. We propose an experimental paradigm to cleanly identify such theoretical relationships. In particular, we focus on overplacement and we find that, as predicted, cognitive uncertainty is inversely related to overplacement. Exogenously manipulating cognitive uncertainty through compound choices, we are able to show a causal relationship with overplacement. Evidence on these relationships allows to link overplacement with other behavioral anomalies explained through cognitive uncertainty
Keywords: D91; C91; D83; 330; Cognitive Uncertainty; Overconfidence; Overplacement; Cognitive Noise; Experiments